1987
DOI: 10.1177/014860718701100128
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the route of nutrient delivery on gut structure and diamine oxidase levels

Abstract: Diamine oxidase (DAO) is an intestinal mucosal enzyme which serves as a marker of cellular maturity and integrity in ontogeny and after mucosal injury in the gastrointestinal tract. Since total parenteral nutrition is known to result in intestinal hypoplasia, this study was done to determine the effect of enteral and parenteral delivery of nutrients on gut structure and DAO levels. Central venous catheters were placed in 27 Sprague-Dawley rats (180-260 g), which received nutrients for 12 days via parenteral nu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0
1

Year Published

1988
1988
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(28 citation statements)
references
References 4 publications
1
26
0
1
Order By: Relevance
“…Similar ly, Laganiere et al [25] found in dogs that there was not a close correlation between the morphological and functional patterns along the intestinal tract. These findings are also consistent with our previous observations in rats receiving total parenteral nutrition that the diminished intestinal DAO activity did not correlate directly with villus height [19]. Furthermore, Guedon et al [29] found that brush border enzyme activity decreases dur ing fasting in humans without gross morpho logical changes.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Similar ly, Laganiere et al [25] found in dogs that there was not a close correlation between the morphological and functional patterns along the intestinal tract. These findings are also consistent with our previous observations in rats receiving total parenteral nutrition that the diminished intestinal DAO activity did not correlate directly with villus height [19]. Furthermore, Guedon et al [29] found that brush border enzyme activity decreases dur ing fasting in humans without gross morpho logical changes.…”
Section: Discussionsupporting
confidence: 91%
“…Such factors include age, vitamin deficiency, endocrine function, pregnancy, diet, malignancy and medications [3,[19][20][21][22], The extent of intes tinal disease and previous intestinal resec tion are obviously important. Whether loca tion of intestinal disease is an important determinant of intestinal and serum DAO activity is another consideration.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Die enterale Na È hrstoffzufuhr ist die physiologische Alternative zur parenteralen Erna È hrung, wobei insbesondere ihre Auswirkung auf die Integrita È t der Darmmukosa hervorzuheben ist [3±7]. Wa Èhrend die Gabe enteraler Erna Èhrung die Darmschleimhaut schu È tzt, kommt es nach 10ta Ègiger totaler parenteraler Erna È hrung zur Ru È ckbildung der Darmmukosa auf 50% ihres Ausgangsvolumens [8]. Die trophischen Effekte selbst geringer Mengen enteraler Erna Èh-rung sind gut dokumentiert [9].…”
Section: Die Rolle Des Gastointestinaltraktsunclassified
“…No comparable studies have been performed using the enteral feeding route, although an increasing body of data suggests that the benefits of enteral nutrition, particularly immunological, are greater than those of isocaloric amounts of parenteral nutrition. 20,21 Caution must be taken when data obtained from patients with gastrointestinal malignancies is extrapolated to the head and neck cancer patient. However, when the postoperative complication rate in high-risk patients (based on PNI) is taken into consideration, we believe it appropriate to advocate delaying surgical procedures in this group for 10 days while preoperative nutritional support is provided, preferably via nasogastric tube feeding.…”
Section: Should Treatment Be Delayed While Nutritional Deficits Are Cmentioning
confidence: 99%